THE LEVEL OF DEPRESSION IN DIABETES MELLITUS PATIENTS WHO EXPERIENCE DIABETIC FOOT ULCERS - Dyah Widodo (Poltekkes Kemenkes Malang, 2021)
Diabetes mellitus is a condition that causes increased blood sugar levels. Diabetes mellitus can cause complications, one of which is diabetic foot ulcers, and can affect psychological changes, one of which is depression. The aim of this study was to determine the level of depression in diabetes mellitus sufferers who experience diabetic foot ulcers. The research design used was a descriptive survey using total sampling techniques. The results of the study showed that almost half of the respondents, namely 16 people (47%) experienced mild levels of depression, almost half of the respondents 13 people (38%) experienced minimal levels of depression, and a small number of respondents 5 people (15%) experienced moderate levels of depression. It is hoped that the clinic can create a psychological counseling program for diabetic foot ulcer sufferers so that it can reduce the risk of depression.